Responsabildade civil do advogado pela perda de uma chance - Paula, Danilo Alves de [UNESP] (2015)
This research is aimed at systematic analysis of tort lawyer for damages cause to the client, however, will not be any damage that will be covered, but one in which the lawyer misses an opportunity to get a chance stop or a loss, as if elapse let the deadline for an appeal. Thus, it is necessary to approach the theory of liability for loss of a chance, which fits into a new line of liability with perfect connection to the Brazilian legal system. It will be found that the possibility of applying the above theory to blame the lawyer, go through the delimitation and restriction of its scope, ie in focus if it is essential to check if there was effectively lost profits, not just the probability of success, it being understood that the mere hypothesis and a tiny probability does not characterize the responsibility of the proponent. Finally, the quantification of the damage arising to the customer will be addressed as a result of inertia, prescription or decadence that the lawyer gave cause